2019
DOI: 10.33800/nc.v0i14.201
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the genus Audantia of Hispaniola with description of four new species (Reptilia: Squamata: Dactyloidae)

Abstract: We revise the species of Audantia, a genus of dactyloid lizards endemic to Hispaniola. Based on our analyses of morphological and genetic data we recognize 14 species in this genus, four of which we describe as new species (A. aridius sp. nov., A. australis sp. nov., A. higuey sp. nov., and A. hispaniolae sp. nov.), and two are resurrected from the synonymy of A. cybotes (A. doris comb. nov., A. ravifaux comb. nov.). Also, we place Anolis citrinellus Cope, 1864 in the synonymy of Ctenonotus distichus (Cope, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Since most of the commonly used mtDNA markers seem to be relatively fast evolving, they are well-suited to the detection of genetic divergences among recently split taxa. We even tend to find more clades in an mtDNA tree than are supported by other evidence lines, such as external morphology, hemipenial morphology in squamate reptiles, or bioacoustics in frogs [26]. On the other hand, if the mtDNA data do not indicate any genetic structuring among the studied populations, then it can safely be concluded that there is no evidence for the recognition of more than one taxon for this set of populations.…”
Section: Introductionmentioning
confidence: 48%
“…Since most of the commonly used mtDNA markers seem to be relatively fast evolving, they are well-suited to the detection of genetic divergences among recently split taxa. We even tend to find more clades in an mtDNA tree than are supported by other evidence lines, such as external morphology, hemipenial morphology in squamate reptiles, or bioacoustics in frogs [26]. On the other hand, if the mtDNA data do not indicate any genetic structuring among the studied populations, then it can safely be concluded that there is no evidence for the recognition of more than one taxon for this set of populations.…”
Section: Introductionmentioning
confidence: 48%
“…Also, we followed Köhler (2012) to name the colors in our description. In addition, we follow taxonomy established by Poe (2013) which unlike (Köhler et al, 2019), regards Anolis as a valid genus for Dactyloid lizards from Hispaniola.…”
Section: Morphological Revisionmentioning
confidence: 99%